Developing Project Schedule in Telecommunication Projects Using Critical Path Method (CPM) - Kusumadarma, Indri Alvi; Pratami, Devi; Yasa, I Putu; Tripiawan, Wawan (International Journal of Integrated Engineering, 2020)
Increased public demand for stable internet network services requires companies engaged in telecommunications to always improve their technological capabilities. One way to improve technological capability is to use basic materials or supporting materials, that is fiber optics (FO). PT. XYZ is a company engaged in the field of telecommunications in several years ago. In general, projects in PT. XYZ experience more frequent delays, one of the most influencing factors that they are not applying the method appropriate to the type of project. If the project schedule does not use a method that is appropriate to the type of project being undertaken, then the result is a delay in the implementation of the project. In a project with small or large scopes, processes such as defining activities, sorting activities, estimating duration and making the Schedule Model are so closely tied to each other that they can be viewed as a Single Process that can be done/done by a person in a relatively short period of time. Therefore, this study focuses on the design of the feeder cabling project schedule in STO Nanjung by using CPM method. The calculation results using the CPM method indicate that the completion time of the Feeder FO cable project is 46 days with 16 critical activities.